Design of a Facility for Tsunami Run up Generation to Study Tsunami and Seawall Interaction - Warniyati Warniyati; Radianta Triatmadja; Nur Yuwono; David S. V. L Bangguna (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2019)
Experimental researches on the tsunami in the laboratory have been conducted using various methods. The use and techniques of tsunami wave generator depend on the objective of the tsunami observation to be conducted. When the objective is the scouring at the downstream of a seawall, the use of a short flume with control discharge seems to be appropriate. A valve with a mechanic controller was equipped to control the discharge from a reservoir into the flume. A numerical simulation of discharge into the flume and the overflow above the seawall was conducted to determine the dimension of the tsunami flume and its generator before construction. The experiments were conducted to simulate the hydrograph of tsunami overflow above the seawall model. The numerical hydrograph is found to be comparable with the experimental hydrograph. This indicates that the tsunami wave generator is capable of simulating tsunami hydrograph and ready for further use of simulations.